Neighbor Selection Protocol for Heterogeneous Information Dissemination in Opportunistic Networks - Halikul, Lenando; Abdallah Hassan, Gharin; Johari, Abdullah; Adnan, Shahid Khan (2015)
In Opportunistic Networks, information forwarding takes place when nodes are in communication range. Absence of knowledge on network topology prior information forwarding poses a compelling challenge in Opportunistic Networks. In these networks, disconnected mobile peers use mobility to opportunistically and dynamically connect to each other in order to disseminate heterogeneous information towards the intended destination. Flooding disseminates information to all nodes in range. Hence, it achieves high delivery performance. However, this form of dissemination congests the network and create considerable amount of network overheads. In this paper, a social-based neighbor selection protocol is proposed to enhance the heterogeneous information dissemination through peer-topeer interaction in opportunistic Networks. Neighbor is selected based on social structure formulated by Frequency in Range, Frequency of Interaction metrics and Heterogeneity of information. A high valued metric peer from the list of candidate peers is selected as potential forwarder to disseminate information. The delivery performance impact of our protocol on information dissemination was investigated and has been analyzed in customized simulation tool. Experimental results showed that, the proposed neighbor selection protocol achieved delivery performance close to random selection in flooding and reduced 88.25% push overhead incurred during dissemination.